Clinico-experimental study of the effect of the goitrogenic effect thiocyanante (Revista Española de Fisiología, 1970)
Variations in goiter occurrence and rate of thiocyanate elimination in uriníƒe were studied periodically during one year in a group of students of both sexes currently living in an area where goiter is endemic. The mean valúes of thiocyanate elimination during each period sho- wed up being significantly higher in the group of students from the goiter area than the corresponding valúes for a control group of students, furthermore, those valúes for the sub- jects from the goiter area reached their máximum at the time of the year when the cows of the zone (whose milk the subjects drank regularly) were fed on a higher amount of tumips than at any other time of the year. High concentration of thiocyanate were also found in tur- nip, and when thiocyanate content was determined in the milk of cows from the goiter area and cows from a non-goiter area and the results were compared, the former showed up having a significantly higher thiocyanate concentration in their milk. The experimental study of anti- thyroid and goiter-inducing effects was also undertaken in a group of guinea pigs fed for a period of 30-90 days on turnip, and although goiter induction could not be demonstrated, a considerable inhibition of I131 uptake by the thyroid was apparent, this inhibition being perhaps related with the hiph thiocyanate concentration in blood. Paradoxically, determina- tion of thyroid I127 showed much higher valúes for the experimental group of animáis than for the control groups, which would supposedly be against the discharge effect currently attri- buted to thiocyanate. A supplement of iodine in the diet of the animal subjects had no effect modifying these results.The results of the present investigation suggest the existence of a sufficient iodine ingesta in the goiter area under study and tum our attention toward thiocyanate as a probable goiter- inducing agent, although not the only one, the effect would consist of an interaction of thio cyanate with other goitrogenous substances, wich would result in an interference with some of the phases of the hormone synthesis process.It is concluded that determination of thiocyanate elimination in uriníƒe can guide us toward a better knowledge of goitrogenous substances present in the diet.